Pengaruh Zat Ekstraktif Beberapa Tumbuhan Terhadap Mortalitas Rayap Tanah (Coptotermes curvignathus Holmgren) - Fahriza Luth (Paspalum: Jurnal Ilmiah Pertanian, 2020)
Subterranean termites are a group of termite that causes economical loss in the timber and crop cultivation business. In Indonesia, subterranean termites are found attacking garden plants and forest plants such as coconut tree, cocoa tree, palm oil tree, and pine tree. Besides, subterranean termites also damage a lot of construction buildings which are made from wood. In Indonesia, it is difficult to effectively prevent the growth of subterranean termite. One of methods to improve wood durability towards subterranean termite threat is to preserve the wood. Sengon tree bark extract, soursop leaf and tobacco leaf are considered to be used as natural preservatives. This research is aimed to find out the effect of extractives of sengon wood, soursop leaf, and tobacco leaf on the mortality of subterranean termite, and this research is aimed to find out which extract substance that has the most retention, mostly affects subterranean termite mortality, and has the least weight loss. This research used an experimental method carried out in the laboratory, using a complete randomized design design, with four treatments that were repeated five times.\ The results showed that the extractives of sengon bark, soursop leaves and tobacco leaves had an effect on reducing the mortality rate of soil termites but were not significantly different in the retention rate. However, tobacco leaf extractive substance has the most effect in reducing the intensity of subterranean termite invasion and causing the least damage.